Comparative efficacy and safety of glucose-lowering drugs in children and adolescents with type 2 diabetes: A systematic review and network meta-analysis - Wu, Sijia; He, Yina; Wu, Yutong; Ji, Yiman; Hou, Lei; Liu, Xinhui; Ge, Yilei; Yu, Yuanyuan; Yu, Yifan; Wei, Yun; Qian, Fengtong; Luo, Qingxin; et al. (Frontiers in Endocrinology, 2022)
Abstract Objective Type 2 diabetes is more common in adults, but is becoming the major concern in children and adolescent recently. This study aimed to provide additional pharmaceutical management for children and adolescents with type 2 diabetes by assessing the efficacy and safety of several glucose-lowering drugs. Methods Searches were performed in PubMed, Medline, Ovid, Cochrane Controlled Register of Trials (CENTRAL) and ClinicalTrials.gov that reported the efficacy and safety of drugs for children and adolescents with type 2 diabetes. Pooled effects were calculated by frequentist fixed effects network meta-analyses and additive network meta-analyses. Results A total of 12 trials assessing 8 glucose-lowering drugs were included, which composes of 7 trials with monotherapy and 5 trials with combination therapies. Network meta-analysis results showed compared to placebo, saxagliptin+metformin (mean difference (MD) -1.91% [-2.85%, -0.97%]), liraglutide+metformin (MD -1.45% [-1.65%, -1.26%]) and liraglutide (MD -0.90% [-1.35%, -0.45%]) were the top 3 drugs that significantly reduced hemoglobin A1c (HbA1c). Sitagliptin+metformin, dapagliflozin, exenatide-2mcg, linagliptin-5mg, metformin, exenatide-5/10mcg, glimepiride and sitagliptin also showed significant reduction in HbA1c. There were no significant differences between treatments in the incidence of adverse events, except that liraglutide+metformin had significant adverse effect such as abdominal pain. In addition, dapagliflozin, sitagliptin+metformin and saxagliptin+metformin showed better efficacy compared with FDA-approved drugs. Conclusions The top 10 treatments of type 2 diabetes in children and adolescents aged 10-17 years were saxagliptin+metformin, liraglutide+metformin, liraglutide, dapagliflozin, exenatide-2mcg, sitagliptin+metformin, linagliptin-5mg, linagliptin-1mg, metformin and exenatide-5/10 mcg.